The importance of being chemical affinity. part v: the fruits (2014)
Through the meticulousness in experimentation, the incorporation of discoveries in physics and the application of the logic of algebra to make chemistry´s language systematic and universal, the level of thought achieved in chemistry during 18th century gave a foundation to the discipline that would allow it to evolve and transform. The discovery, comprehension and application of electricity in the 19th century supplied chemistry with analogous units, which in turn, facilitated increased understanding of the field and permitted the proposal of new theories. Developments in thermodynamics allowed for the presentation of qualitative scales of affinity and electronegativity. The discovery of the atom and electron and the emergence of quantum physics restructured chemical thought, permitting for the establishment, in the first half of the 20th century, of the first quantitative scale of electronegativity, which offered chemistry a new dynamism, facilitating the proposal of other scales, based on diverse approaches.